An Investigation of Aluminium & Magnesium Alloy with Interlayer Using Diffusion Bonding - Renjith Nimal, R.J. Golden; Sivakumar, M.; Esakkimuthu, G. (International Journal of Psychosocial Rehabilitation, 2019)
This work is conducted to obtain better understanding and characterization of the diffusion bonding of similar and dissimilar metals. It also aimed to obtain optimum parameters for diffusion bonding of aluminium coating over magnesium alloy with Aluminium alloy. This work aims at developing a simple method to obtain diffusion bonding joints at relatively not low cost. On one hand, the research is intended to establish a method. It is not much easy to perform fusion welding of dissimilar metals of entirely two different metal species and getting a sound joint. Therefore, an alternate method is essential, for this solid state welding is the right method, among several such processes diffusion bonding is one of the solid state welding process suitable for joining aluminium coating over magnesium alloy with Aluminium alloy. On the other hand, the method is to serve as the basis for further research for production of application oriented components and parts. These two metals are jointed inside the die after finishing surface treatment. Then the die is kept inside the diffusion bonding machine by varying the time, temperature, pressure by means of load. Hot press diffusion bonding equipment is fabricated and verified with experiments so that it is capable of rendering accurate diffusion bonding joints with facilities to measure parameters and to investigate the super plastic diffusion bonding joints with interlayer. This method is devised to study the physical phenomena that have significant influence on diffusion bonding such as time, temperature, pressure on joints and metallurgical characteristics. Tensile and shear tests are to be conducted.